Impact of Board Size , CEO Duality, and Independent Commissioner on the Format of Sustainability Reports in Banking Companies - Arifah, Aliya Murthi; Azmiyanti, Rizdina (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
Purpose: This study investigates the impact of board size, CEO Duality, and the independent commissioner board on the format of sustainability report in banking company. Methodology: A quantitative method using logistic regression analysis was applied to a sample of 31 banking companies listed on the Indonesia Stock Exchange from 2022 to 2024. Results: Board size and independent commissioner boards significantly influence the format of sustainability reports, while CEO duality has no impact. Findings: Companies with larger boards and more independent commissioners are more likely to publish standalone sustainability reports. Novelty: The research provides insights into how corporate governance factors, like board composition, influence sustainability reporting, a topic underexplored in the Indonesian banking sector.. Originality: This study contributes by focusing on banking companies in Indonesia and the application of governance variables in sustainability reporting formats.Conclusion: Board size and independent commissioners are key drivers of sustainability report formats, while CEO duality does not significantly influence the format. Type of Paper: Empirical Research article